Could perinatal asphyxia induce a synaptopathy? : new highlights from an experimental model - Herrera, María Inés (2017)
Fil: Herrera, María I. Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina